An investigation of multiple jet acetylene flames - Leite, A. O.P.; Ferreira, M. A.; Carvalho, J. A. (Elsevier, 1996)
The interaction between turbulent acetylene flames was investigated experimentally by the analysis of their visible lengths. The study involved 1, 2, 3 and 5 turbulent flames formed by parallel vertical jets whose relative distance was varied. The tube internal diameters were 1, 2, 3 and 4.4 mm. The results quantify the increase of flame length of multiple jets of equal injection tube radii and equal initial velocities as the flame separation distance decreases and as the number of jets increases. An empirical formula relating the length of multiple jet flames to that of the individual flame of same burner diameter was derived. Results of experiments performed with parallel burners inclined of 45° in relation to the vertical direction are also presented.